On the Utopia of The End of Alienation. Hannah Arendt (Mis)reading Simone Weil ̶ and Karl Marx - Iakovou, Vicky (Labyrinth, 2023)
The starting point of this paper is Hannah Arendt's positive comment on Simone Weil's La condition ouvrière, in The Human Condition. I first offer a brief reconstruction of Arendt's interpretation of Marx's analysis of labor which is the context in which the above-mentioned comment appears. This interpretation is based, I claim, on a (mis)reading which consists in a rather systematic blurring of the distinction between labor as a universal and irreducible human activity and labor in its historically determined capitalist form, which is the object of Marx's critique, i.e., alienated labor. Following that, I discuss Weil's construal of labor and I shed light on its affinities with the Marxian problematic. My aim is to show that Arendt's comment does not do justice to the problems that Weil addresses both with and beyond Marx.